Light-chain proximal tubulopathy: a retrospective study from a single Chinese nephrology referral center - Xin Wang; Xiao-juan Yu; Su-xia Wang; Fu-de Zhou; Ming-hui Zhao (Renal Failure)
Background Light-chain proximal tubulopathy (LCPT) is a rare disease characterized by the accumulation of monoclonal light chains within proximal tubular cells. This study aimed to investigate the clinical characteristics of LCPT from a single Chinese nephrology referral center.Methods Patients with kidney biopsy-proven isolated LCPT between 2016 and 2022 at Peking University First Hospital were retrospectively included. Clinical data, kidney pathological type, treatment, and prognosis were analyzed.Results Nineteen patients were enrolled, the mean age at diagnosis was 57 ± 11 and the sex ratio was 6/13 (female/male). Mean proteinuria was 2.44 ± 1.89 g/24 hr and the mean estimated glomerular filtration rate (eGFR) at the point of biopsy was 59.640 ± 27.449 ml/min/1.73 m2. κ-restriction (84%) was dominant among LCPTs. An abnormal free light chain ratio was observed in 86% of the patients. Proximal tubulopathy with cytoplasmic inclusions accounted for the majority (53%), followed by tubulopathy associated with interstitial inflammation reaction (26%), proximal tubulopathy without cytoplasmic inclusions (16%), and proximal tubulopathy with lysosomal indigestion/constipation (5%). One patient presented with acute kidney injury and 16 patients presented with chronic kidney disease. Regarding follow-up, patients received bortezomib-based or R-CHOP chemotherapy or supportive treatment only. The mean follow-up time was 22 ± 16 months, and the mean eGFR was 63.098 ± 27.439 ml/min/1.73 m2 at the end of follow-up. These patients showed improved or stable kidney function.Conclusions This is the first case series report of LCPT in four different pathological types in northern China. Clone-targeted chemotherapy may help preserve the kidney function in these patients.